ANALISIS DATA LAPORAN PENGELOLAAN APBN 2019 - Felianti Dwi Wulandari (Universitas Halu Oleo, 2020)
The purpose of this paper is to analyze Indonesia's 2019 National Income through the 2019 State Budget management report data. The analysis of this article uses a qualitative descriptive analysis method based on data sourced from the Central Statistics Agency. The results of the analysis show that the 2019 Indonesian National Income In the 2019 Draft State Budget, the Government proposes an exchange rate assumption of IDR 14,400 / 1USD, and it is agreed to be IDR 14,500 / 1USD at the Assumption Committee Meeting. The 2019 State Budget tax revenue is targeted at IDR 1,786.4 trillion or a growth of 15.4 percent from the outlook for the 2018 State Budget with a broad tex ratio of around 12.2 percent. It can be concluded that the 2019 state revenue target is the optimal target.